The Shaadi set-up : a novel - Vale, Lillie (G.P. Putnam's Sons, 2021)
"In this witty and heartfelt rom-com debut for fans of Jasmine Guillory, Emily Henry, and Tessa Bailey, an Indian American woman signs herself and her boyfriend up for a matchmaking site to prove they're a perfect match, only to be paired with her ex instead"--